2013
DOI: 10.1523/jneurosci.4058-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Hierarchy within the Parietofrontal Network in Stimulus Selection and Attention Control

Abstract: Although we are confronted with an ever-changing environment, we do not have the capacity to analyze all incoming sensory information. Perception is selective and is guided both by salient events occurring in our visual field and by cognitive premises about what needs our attention. Although the lateral intraparietal area (LIP) and frontal eye field (FEF) are known to represent the position of visual attention, their respective contributions to its control are still unclear. Here, we report LIP and FEF neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
123
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(140 citation statements)
references
References 50 publications
17
123
0
Order By: Relevance
“…A more direct demonstration that attentionrelated modulation of the LIP response is evoked by FEF input would require LIP recordings and precisely targeted FEF inactivations, which would by themselves cause deficits in any visual search task (Wardak et al, 2006). Nevertheless, our data provide direct and causal evidence consistent with Ibos et al (2013), implicating FEF as a source of input that enhances the visual responses of LIP neurons to behaviorally relevant events.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…A more direct demonstration that attentionrelated modulation of the LIP response is evoked by FEF input would require LIP recordings and precisely targeted FEF inactivations, which would by themselves cause deficits in any visual search task (Wardak et al, 2006). Nevertheless, our data provide direct and causal evidence consistent with Ibos et al (2013), implicating FEF as a source of input that enhances the visual responses of LIP neurons to behaviorally relevant events.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, our results suggest that the effect of FEF-EM on LIP can be observed under conditions of selective spatial attention (toward the LIP RF), but not during divided attention. Ibos et al (2013) compared responses in FEF and LIP neurons during an attention-orientation target detection task, in which monkeys were cued to attend to one hemifield to detect a target embedded in a stream of distractors. On the basis of the analysis of the neuronal latencies and the proportions of cue-and target-selective neurons in FEF and LIP, the authors hypothesized that enhancement of the LIP response to behaviorally relevant stimuli may be the result of top-down influences originating in the FEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In the parietal lobe, the location and function of subregions involved in eye movements and attention have been studied intensively, but are still not so well known. 26,27 The parietal lobe and more particularly its posterior part, the PPC, are involved in the control of saccades and attention. In humans and nonhuman primates, the PPC includes the intraparietal sulcus (IPS) extending from the post-central sulcus anteriorly to the parieto-occipital sulcus posteriorly (Figure 1).…”
mentioning
confidence: 99%
“…For example, single cell recordings in the macaque during the execution of complex tasks have revealed that a wide range of task features, including task rules, cues and stimuli features can be coded by the same set of cells (Duncan, 2001;Ibos et al, 2013). Moreover, this coding is dynamic, such that neurons are reallocated to the most important task at hand, at the timescale of single trials (Kadohisa et al, 2013;Stokes et al, 2013).…”
Section: From Local To Global Models Of Brain Activation Associated Wmentioning
confidence: 99%